2009
DOI: 10.1159/000180915
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase II Study of Pegylated Liposomal Doxorubicin in Combination with Vinorelbine as First-Line Treatment in Elderly Patients with Metastatic Breast Cancer

Abstract: Background: This multicenter phase II trial was conducted to analyze the clinical activity and toxicity of the combination of pegylated liposomal doxorubicin and vinorelbine as first-line treatment in elderly patients with metastatic breast cancer. Patients and Methods: From August 2002 to August 2004, 42 patients with metastatic breast cancer were recruited for treatment with pegylated liposomal doxorubicin 40 mg/m2 intravenously (i.v.) on day 1 and vinorelbine 30 mg/m2 i.v. on days 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…21 Two trials evaluated a first-line combination regimen of PLD plus vinorelbine in elderly patients, obtaining fairly good response rates of 36% 22 or 50%, 23 conflicting TTP of 4 months 22 or 8 months, 23 and higher rates of hematological toxicity (neutropenia 15% grade 3 and 11% grade 4) with 10% of febrile neutropenia, and gastro-intestinal toxicity. 23 The authors' conclusion that "the combination of PLD and vinorelbine is active and well tolerated in elderly patients" should be considered with caution since they applied an inferior age limit of 65 23 or even 60 years, 22 while 70 years is believed to be the real turning point for age related physiologic changes. 13 Since the start of this trial, also a non-pegylated version of liposomal doxorubicin has been registered for breast cancer in association with cyclophosphamide, but, to our knowledge, data on elderly patients are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…21 Two trials evaluated a first-line combination regimen of PLD plus vinorelbine in elderly patients, obtaining fairly good response rates of 36% 22 or 50%, 23 conflicting TTP of 4 months 22 or 8 months, 23 and higher rates of hematological toxicity (neutropenia 15% grade 3 and 11% grade 4) with 10% of febrile neutropenia, and gastro-intestinal toxicity. 23 The authors' conclusion that "the combination of PLD and vinorelbine is active and well tolerated in elderly patients" should be considered with caution since they applied an inferior age limit of 65 23 or even 60 years, 22 while 70 years is believed to be the real turning point for age related physiologic changes. 13 Since the start of this trial, also a non-pegylated version of liposomal doxorubicin has been registered for breast cancer in association with cyclophosphamide, but, to our knowledge, data on elderly patients are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…In details, the PLD/VNB combination was recently employed in two phase II trials in heavily pretreated patients, yielding a response rate of 36% and 39%, without any cardiac toxicity [37,38]. Two more recent reports with PLD/VNB combination as first-line treatment in elderly patients confirmed the good overall clinical response rate (36% and 50%, respectively), and t he high tolerability of the regimen [39,40] suggesting, due to the safety profile of the combination, the employment also in such "frail" patient population.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of phase II trials have been performed which have generally shown encouraging activity with an acceptable safety profile (Table 3). Examples include Paclitaxel 30–37 Docetaxel; 3846 Doxorubicin; 4751 Epirubicin 5254 Mitoxantrone; 5557 Pegylated Liposomal Doxorubicin; 14,5861 Gemcitabine; 6273 5-Fluorouracil; 7479 platinum compounds; 8083 and Capecitabine, 8488 which will be separately discussed. Several triplets have also been investigated but increased toxicity should be expected.…”
Section: Introductionmentioning
confidence: 99%